Effect of Coarse Aggregate Size Variation on Compressive Strength of Concrete along the Length of Kali Gandaki River (Shikshya Sandesh, 2023)
The Kali Gandaki River is renowned for its diverse geological composition, providing a unique opportunity to examine how the inherent characteristics of coarse aggregates impact concrete performance in terms of compressive strength. This research delved into the influence of varying coarse aggregate sizes on the compressive strength of concrete obtained from different points along the Kali Gandaki River. Multiple samples of coarse aggregates were gathered from distinct geological regions along the river. The study adopted a concrete mix design for M20, and concrete cubes were manufactured with coarse aggregate sizes ranging from 10mm-16mm, 16mm-20mm, 20mm-25mm, to 25mm-31.5mm. All sample sets underwent compressive strength testing after 7 and 28 days of curing. The results revealed that, under identical curing conditions and water-cement ratios, the compressive strength of the produced concrete increased with the aggregate size, reaching a peak at 25mm. Additionally, among the surveyed locations, namely Ramdi Ghat, Khada Ghat, Pakhichaur Hungi Ghat, and Belchaur Ghat, Belchaur Ghat exhibited superior performance in compressive strength. The findings of this work aim to contribute valuable insights to the field of concrete technology and construction industry.